Factors Causing Motor Vehicle Theft and Efforts to Handle It in Rokan Hilir Jurisdiction - Syahputra, Hendra; Kusno, Kusno; Siregar, Ahmad Ansyari (International Journal Labs, 2024)
The purpose of this study is to determine the factors of criminal offenders committing motor vehicle theft and efforts to overcome Curanmor crime in the jurisdiction of Rokan Hilir. The type of research used is the juridical-empirical research method, which is a process of research and understanding based on methodology that investigates a social phenomenon and human problems. Results of Discussion: first, Factors causing the occurrence of motor vehicle theft include: 1. Economic Factors, This factor occurs due to pressure on the fulfillment of basic daily needs; 2. Habitual factor, This factor is influenced because of behavior that occurs repeatedly and continuously so it is difficult to stop it. ; 3. Environmental Factors, Environmental factors/association greatly influence a person to do or not do something. Do something because in the environment is accustomed to committing criminal acts such as curanmor, then the environment greatly influences curanmor perpetrators to commit the same crime because the environment is very supportive.; 4. Lifestyle Factors, This factor is caused by the fulfillment of additional needs, outside of the general need to improve lifestyle in the community. Second, efforts to overcome the crime of theft of motor vehicles (curanmor) in the jurisdiction of Rokan Hilir are carried out in 2 ways, namely by preventive and repressive efforts.